IDENTIFIKASI KUALITAS RUANG TERBUKA PUBLIK DI PERMUKIMAN KOTA (STUDI KASUS : TAMAN LINGKUNGAN DI KAWASAN BSD CITY, KOTA TANGERANG SELATAN) - Elvareta -; Yohanes Basuki Dwisusanto (Riset Arsitektur (RISA), 2023)
Abstract - Since the beginning of the COVID-19 pandemic, South Tangerang City Government has temporarilyclosed City Parks 1 and 2. With the closure of city parks, people are looking for alternative public open spaceson a smaller scale, namely neighborhood parks. The focus of the research will be on neighborhood parks in theBSD City, Taman Perdamaian dan Taman Kesehatan. Both objects of this study have the same position as anactive neighborhood park. Currently the condition of Taman Perdamaian has decreased in physical quality.Meanwhile, the condition of Taman Kesehatan looks deserted by visitors even though the facilities are very wellmaintained. This study wants to identify more deeply the quality of the two public open spaces in terms ofphysical elements and their activities to find out what factors influence the success of the two neighborhoodparks as public open spaces in urban settlements. This research is descriptive qualitative. Information wascollected by field observations related to physical elements and their use in the two study objects. Furthermore,questionnaires and interviews were distributed to users, to obtain perception data as a basis for identifying thequality of the two public open spaces. Based on the analysis, it is known that the Taman Perdamaian hasmanifested three qualities that contribute to the overall structure of a place, namely permeability, variety, andphysical legibility. With the realization of these three qualities, the park's success can be seen in attracting moreusers. Meanwhile, in Taman Kesehatan of the three qualities that stand out, only permeability and the moredominant manifestation of visual suitability and richness that are more focused on spatial details. This answerswhy Taman Kesehatan is underutilized, namely because of the lack of embodiment of the quality of diversity andquality of legibility.Keywords: public open space in settlements, neighborhood park, quality of public open space